Efeitos renais induzidos pelo sobrenadante de macrofagos estimulados pelo veneno da Crotalus durissus cascavella e determinação de suas frações que induzem toxicidade renal - Martins, Alice Maria Costa (2002)
The genus Crotalus is responsible annually for approximately 1500 cases of snakebite in Brazil. The most common complication in the lethal cases is acute renal failure, but the effects are not completely well understood. In this work, we have examined the renal effects caused by the supernatant of macrophages stimulated by Crotalus durissus cascavella venom as well as the potential role of the inflammatory mediators. We used Sephadex G75 and RP- HPLC chromatography to isolate and purify crotoxin (phospholipase A2 and crotapotin), convulxin, gyroxin and crotamine from Crotalus durissus cascavella venom to investigate their effects on renal physiology in the isolated perfused rat kidney method. Rat peritoneal macrophages were collected and placed in a RPMI médium and stimulated by Crotalus durissus cascavella venom (1, 3 or 10 pg/mL) for 1 hour. They were washed and kept in this culture for 2 hours. The supernatant (1mL) was tested in the isolated perfused rat kidney method. The first 30 min of each experiment were used as an internai control, and the supernatant was added to the system after this period. All experiments lasted 120 min. The lowest concentration of venom (1 pg/mL) was not statistically different from the control values. The most intense effects were seen with 10 pg/mL for all renal parameters. The infusion of the supernatant of macrophages stimulated with the venom (3 or 10 pg/mL) increased the perfusion pressure (PP), renal vascular resistance (RVR), urinary flow (UF) and glomerular filtration rate (GFR). The percent of total and proximal sodium, potassium and chloride tubular transport decreased. Cyclohexamide (CHX, 10'5M), dexamethasone (Dexa, 10'5M), quinacrine (Quinac, 10 5M), thalidomide (TALID, 1,5x10 _5M) and pentoxifylline (PTX,5x10’5 M) blocked all the renal effects promoted by this venom. Indomethacin (Indo, 10‘5M) and nordiidroguaretic acid (NDGA,10'6M) reversed almost all functional changes, except for PP and RVR. Platelet activated factor antagonist (WEB 2086, 10’5 M) blocked only GFR and UF. These results suggest that macrophages, stimulated with Crotalus durissus cascavella venom, released mediators capable of promoting nephrotoxicity in vitro. Crotoxin (5 pg/mL) and gyroxin (5 pg/mL) altered all the renal parameters evaluated, but giroxin produced a minor effect compared to crotoxin. Crotamine affected vascular and glomerular function but not tubular. Convulxin (5 pg/mL) did not change renal parameters. Phospholipase A2 (5 pg/mL) and crotapotin (5 pg/mL), separately, caused mild effects on renal physiology when compared to the crotoxin complex. These results indicated that crotoxin is the main component responsible for acute nephrotoxicity caused by Crotalus durissus cascavella venom.